FURNITURE AS ARCHITECTURAL ELEMENT - Temelkovski, Branko (Faculty of Design and Technology of furniture and interior – Skopje, 2022)
The aim of this paper is to analyze the concept of incorporating furniture and equipment into architectural design, a concept familiar to both vernacular and contemporary architecture. The first section explores the symbiosis of architecture and furniture/equipment in traditional Macedonian architecture from the 19th century. Such a holistic approach was also perceived in the ideas of modernists from the beginning of the 20th century, who were strongly inspired by vernacular architecture. Further, various ideas that developed persistently and progressively all the way to the contemporary era were observed from the current perspective, by investigating their original approaches of reaffirming such concepts. For the purpose of this study, several distinctive cases were analyzed in respect of their features relevant to the topic.
International Journal - Wood, Design & Technology
Keywords: architecture, furniture, equipment, integration, holistic approach